Challenge’s Encountered of Paradise Apartelle in Using Technology: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Technology is the application of knowledge to achieve practical goals in a reproducible way.The word technology can also mean the products resulting from such efforts, including bothtangible tools such as utensils or machines and intangible ones such as software. Technologyplays a critical role in science, engineering, and everyday life. A steam turbine with the caseopened is an example of energy technology. Technological advancements have led tosignificant changes in society. The earliest known technology is the stone tool, used duringprehistoric times, followed by the control of fire, which contributed to the growth of the humanbrain and the development of language during the Ice Age. The invention of the wheel in theBronze Age allowed greater travel and the creation of more complex machines. More recenttechnological inventions, including the printing press, the telephone, and the Internet, havelowered barriers to communication and ushered in the knowledge economy. While technologycontributes to economic development and improves human prosperity, it can also havenegative impacts like pollution or resource depletion or may cause social harms liketechnological unemployment resulting from automation. As a result, there are ongoingphilosophical and political debates about the role and use of technology, the ethics oftechnology, and ways to mitigate potential downsides.Based on the overall result, the descriptive method obtained an average of 3.23, 3.07, and3.2, which means. Technology helps Paradise employees in providing and maintaining highstandards.According to the general result based on the employees of Paradise Hotel, technology hasbeen a great help for them to accomplish not lowering the standard rate of their hotel butincreasing it even more.
Keywords: Hospitality Management